PENGARUH PENGGUNAAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS X SMA ADABIAH PADANG - Adidah, Adidah; Thahar, Harris Effendi; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this study is to describe 1) short story writing skill of tenth graders in Padang Adabiah high school without using serial pictures media, 2) describe short story writing skill of tenth graders in Padang Adabiah high school by using serial pictures media, 3) describe the influence of using serial pictures media toward the level of short story writing skills of tenth grader in Padang Adabiah High School. The type of this research is quantitative research done using quasi experimental design. There are three results of the research are (1) short story writing skills of the tenth graders in Padang Adabiah Senior High School without using serial pictures media were in more than enough qualifying with the average score of 67,78. (2) short story writing skills of the tenth graders in Padang Adabiah Senior High School by using serial pictures media were in a good qualifying with the average score of 76.55. (3) based on the t-test at the level of 0.05 obtained thitung > ttabel (5,54> 1,70). Thus, it can be said that H1 is accepted. It means that there is a significant effect of using serial pictures media toward the short story writing skills of tenth graders in Padang Adabiah Senior High School.Kata kunci : pengaruh, media gambar berseri, and cerita pendek